2023
DOI: 10.3390/cancers15133497
|View full text |Cite
|
Sign up to set email alerts
|

Are CT-Derived Muscle Measurements Prognostic, Independ-ent of Systemic Inflammation, in Good Performance Status Pa-tients with Advanced Cancer?

Abstract: The present study examined the relationships between CT-derived muscle measurements, systemic inflammation, and survival in advanced cancer patients with good performance status (ECOG-PS 0/1). Data was collected prospectively from patients with advanced cancer undergoing anti-cancer therapy with palliative intent. The CT Sarcopenia score (CT-SS) was calculated by combining the CT-derived skeletal muscle index (SMI) and density (SMD). The systemic inflammatory status was determined using the modified Glasgow Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is of interest that recent secondary analyses of clinical trial data have reported that systemic inflammation dominates the prognostic value of CT-derived muscle mass for survival outcomes in patients with advanced cancer. 8,9 Therefore, in light of the present observations, a comparison of the relative prognostic value of weight loss and relative skeletal mass in the context of systemic inflammation would be informative.…”
Section: Dear Editormentioning
confidence: 90%
“…It is of interest that recent secondary analyses of clinical trial data have reported that systemic inflammation dominates the prognostic value of CT-derived muscle mass for survival outcomes in patients with advanced cancer. 8,9 Therefore, in light of the present observations, a comparison of the relative prognostic value of weight loss and relative skeletal mass in the context of systemic inflammation would be informative.…”
Section: Dear Editormentioning
confidence: 90%